The Level of the Ability of Designing Inquiry Experiments by Science Student Teachers at Sultan Qaboos University: Some Variables - Balushi, Suleman; Ambosaedi, Abdullah (Jordan Journal of Educational Sciences, 2009)
The study aimed at exploring science student teachers' skills in designing inquiry experiments. The subjects of the study were 82 student teachers joining the B.Sc. and Teacher Qualification Diploma (TQD) programs at Sultan Qaboos University. They were asked to deign six inquiry activities using a designing form, including 14 items each of which dealt with a different inquiry skill: questioning, determining and controlling variables, predicting, planning for materials, observations, measuring, procedures, trials, safety precautions, collecting and representing data, reasoning, and explanations. The findings showed that the student teachers' designing level was weak, especially in controlling variables, trials, explanations, and safety precautions. In addition, the B.Sc. students outperformed TQD students, and biology majors outperformed chemistry and physics majors.